2017
DOI: 10.1016/j.biochi.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Control of adipogenesis by oxylipins, GPCRs and PPARs

Abstract: Oxylipins are bioactive metabolites derived from the oxygenation of ω3 and ω6 polyunsaturated fatty acids, triggered essentially by cyclooxygenase and lipoxygenase activities. Oxylipins are involved in the development and function of adipose tissue and their productions are strictly related to diet quality and quantity. Oxylipins signal via cell surface membrane (G Protein-coupled receptors) and nuclear receptors (peroxisome proliferator-activated receptors), two pathways playing a pivotal role in adipocyte bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 124 publications
0
61
0
1
Order By: Relevance
“…Lipids are essential for biological processes, are important components of signaling pathways, and are closely linked to disease processes. The role of lipid mediators in the pathogenesis of disease, particularly inflammation, is an active, new area of research endeavor [82,83,84,85]. …”
Section: Metabolomics and Immunometabolism Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lipids are essential for biological processes, are important components of signaling pathways, and are closely linked to disease processes. The role of lipid mediators in the pathogenesis of disease, particularly inflammation, is an active, new area of research endeavor [82,83,84,85]. …”
Section: Metabolomics and Immunometabolism Relationshipsmentioning
confidence: 99%
“…Most of the PUFA substrate is esterified within cell membrane phospholipids, but can be rapidly released in response to inflammatory or injury stimuli through the enzyme phospholipase A2 (PLA2) [83]. The released PUFAs are changed through both enzymatic and nonenzymatic activities to form oxygenated derivatives called oxylipins [76,83]. Oxylipins can be divided into eicosanoids (synthesized from C20 PUFAs such as arachidonic acid and EPA) and docosanoids (synthesized from C22 PUFAs such as DHA), and also include linoleic acid oxygenated derivatives such as the HODEs.…”
Section: Metabolomics and Immunometabolism Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo, brite adipocytes stem from progenitors or emerge by direct conversion of mature white adipocytes (22)(23)(24). Several studies have demonstrated the involvement of oxylipins in fat mass development through the modulation of white and brown/brite adipocyte differentiation and activity (25). Mice exposed to diets with high levels of ω6 PUFA during the perinatal period display progressive accumulation of body fat across generations (26).…”
Section: Introductionmentioning
confidence: 99%